INFLASI, TINGKAT SUKU BUNGA, DAN KONSUMSI DI PROVINSI ACEH - Hakim Muttaqim; Hamdani Hamdani; Dasmi Husin (Jurusan Akuntansi Politeknik Negeri Bandung, 2019)
This study aims to look at the effect of inflation and interest rates on public consumption in Aceh province in the long term and short term with the data used are annual data from the above variables starting from 1996 to 2015. The method used is Error Correction Models ( ECM). The results of data analysis in this study using Software Eviews 7 shows that inflation has a significant effect on people's consumption in Aceh Province in the long term and short term, while interest rates only affect the long term.